Juri Lotman’s Typologies of Culture - Salupere, Silvi (Semiotika, 2022)
One central concept in Juri Lotman’s semiotics of culture are cultural typologies, the objective of which is to describe the basic types of cultural codes, define the universals of human culture, and to create “a grammar of culture”, i. e. a unified system of the general structure of the universal characteristics of the “culture of humankind”. Lotman compares culture with a living organism as well as with a work of art, above all emphasizing the dynamicity of culture that is effected by two poles (i. e. consciousnesses) throughout the whole of cultural history: cyclical-continual (mythological) and linear-discrete (historical). The article views Lotman’s different conceptions of cultural typologies as a whole, where one and the same binary opposition is described in different ways and with different emphases, conclusively from which two universal types of culture are drawn out.